Tata Kelola Pariwisata Malaumkarta terhadap Peningkatan Pendapatan Asli Daerah - La Basri; Anita Mambri Binwasef; Masni Banggu; Nur Hidaya (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze the role of the local government and community in managing tourism in Malaumkarta village towards increasing local revenue (PAD) of Sorong Regency. The method used in this research is qualitative research method with the number of informants obtained as many as 7 (seven) people. Data was obtained using observation, interview, and documentation techniques, and then the data was analyzed descriptively based on the sources obtained. The results showed that the government has made every effort to develop tourism in Malaumkarta village by providing facilities and infrastructure to support tourism such as relaxing places (gazebos), public toilets, selling stalls, padang towers, and the construction of other facilities. However, the problem is that until now these facilities have not been used according to their needs, what was planned at the beginning was not implemented, especially the concept of local culture-based development for the Papuan people. In addition, until now the collection of retribution has not been implemented because the government is still focused on implementing development and empowering the community. The government expects good cooperation between the community in managing tourism because the community is the organizer of the sustainability of tourism.